2013
DOI: 10.1007/s10067-013-2176-8
|View full text |Cite
|
Sign up to set email alerts
|

NK cells dysfunction in systemic lupus erythematosus: relation to disease activity

Abstract: Through their cytotoxic capacities and cytokine production, natural killer (NK) cells modulate autoimmune diseases. However, their role in the pathogenesis of systemic lupus erythematosus (SLE) has not been extensively studied. The aim of this study was to analyse the immunophenotypic and functional characteristics of the two major NK cell subsets in SLE and relate them with disease activity. Peripheral blood samples from 44 patients with active (n = 18) and inactive SLE (n = 26) and 30 controls were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 34 publications
8
48
1
Order By: Relevance
“…In agreement with the previous studies [31, 32], we found that the percentages of NK cells and NKT-like cells are decreased in PBMC from SLE patients compared to controls. However, The percentages of T cells were comparable to controls.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the previous studies [31, 32], we found that the percentages of NK cells and NKT-like cells are decreased in PBMC from SLE patients compared to controls. However, The percentages of T cells were comparable to controls.…”
Section: Discussionsupporting
confidence: 93%
“…The interpretation that NK cells in PBMCs are depleted as a result of death, therefore, might be partially flawed, as it could also be a result of NK cell migration to target organs in SLE. NK cell trafficking to SLE target sites could explain the reduction in the percentage of CXCR3-positive NK cells in PBMCs of patients with active disease [65], in line with our data from murine models. As CXCR3 has a role in NK cell trafficking to inflamed organs, this reduction in mature CD56 dim CXCR3-positive cells could, in fact, reflect a shift of these cells from the periphery to target organs.…”
Section: Organ-specific Differences In Sle-looking In the Right Place?supporting
confidence: 82%
“…CD27 High , CD11b Low , CD56 bright immature NK cells have reduced cytotoxic function but increased IFN-g secretion; these cells might be the predominant phenotype in SLE patient PBMCs [49,57,65].…”
Section: Nk Cells In Sle-perennial Underachievers?mentioning
confidence: 97%
“…Roquin san/san mice display decreased IFN-γ mRNA decay leading to chronic circulating levels of IFN-γ and a lupus-like phenotype [2] and offspring from lupus-prone MRL/lpr mice crossed with IFN-gamma −/− mice have reduced autoantibody titers and less severe end-organ disease [3]. In humans, IFNG gene polymorphisms have been identified in SLE cohorts [4,5] and dysregulated NK cells, T cells, and PBMCs from SLE patients produce elevated amounts of IFN-γ that correlate with SLE Disease Activity Index Scores [6-8]. Mechanistically, IFN-γ induces B cell activating factor (BAFF), a protein critical for B cell differentiation, proliferation, and survival that has been identified as a therapeutic target in SLE [4,9].…”
Section: Introductionmentioning
confidence: 99%